A Holistic Approach for Design and Assessment of Building-Integrated Photovoltaics Systems - David Restrepo-Herrera; Walter Martinez; Luz Adriana Trejos-Grisales; Bonie Johana Restrepo-Cuestas (Applied Sciences, 2023)
This article addresses the application of building-integrated photovoltaic (BIPV) systems through the analysis of a case study with different operating conditions and geospatial locations. The research is carried out with customer-made photovoltaic modules supported by computational aids. The results obtained from real-life BIPV installation are contrasted, simulated, and improved through different scenarios where aspects such as software deviation, shadowing influence, installed capacity, and project profitability are analyzed to establish viability pathways for BIPV projects. As a result, the most relevant factors to improve the technical and economic conditions of the BIPV system are the total capacity installed, the use of the available area, and the strategic location of the modules to avoid shading surfaces. In this way, this work addresses the analysis of BIPV systems through the assessment of a case study implemented in a real residential structure in Colombia. The proposed methodology includes simulations to evaluate the solar energy potential considering the elements in the neighborhood of the BIPV system and technical aspects, such as the wiring and power interface, an economical study to find the feasibility of the project, and an analysis of different operating scenarios. As a result, the most important factors that affect the operation of BIPV systems under Colombian weather conditions were identified: total installed capacity, use of the available area, and strategic location of the modules to avoid shading surfaces. Such factors can then be considered in the early stage of designing for future BIPV applications.